219k views
2 votes
Csc^3x-csc^2x-cscx+1=cot^2x(cscx-1)​

User Jack Feng
by
4.8k points

2 Answers

2 votes

Sorry, I messed up. So I changed it.

User GuerillaNerd
by
5.4k points
1 vote

Verify the identity:


csc^3x-csc^2x-cscx+1\qquad =cot^2x(cscx-1)\\\\csc^2x(cscx-1)-1(cscx-1) =\quad \downarrow\\\\(csc^2x-1)(cscx-1)\quad \qquad \ =\quad \downarrow\\\\\bigg((1)/(sin^2x)-(sin^2x)/(sin^2x)\bigg)(cscx-1)\ =\quad \downarrow\\\\\\\bigg((1-sin^2x)/(sin^2x)\bigg)(cscx-1)\qquad \ =\quad \downarrow\\\\\\\bigg((cos^2x)/(sin^2x)\bigg)(cscx-1)\qquad \qquad =\quad \downarrow\\\\\\cot^2x(cscx-1)\qquad \qquad \qquad =cot^2x(cscx-1)\qquad \checkmark

User Acorello
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.